A systematic review of the effects of silvopastoral system on thermal environment and dairy cows’ behavioral and physiological responses - Deniz, Matheus [UNESP]; De-Sousa, Karolini Tenffen; Vieira, Frederico Márcio Corrêa; Vale, Marcos Martinez do; Dittrich, João Ricardo; Daros, Ruan Rolnei; Hötzel, Maria José (Springer Nature, 2023)
Does the silvopastoral system (SPS) promote a satisfactory thermal environment for dairy cows to perform their natural behaviors and perform a suitable thermoregulatory function? To answer this, peer-reviewed articles, written in English and evaluating the effects of silvopastoral systems on thermal environment, dairy cows’ behavior, and physiology were used in this systematic review; additionally, a bibliometric approach was performed. Web of Science and Google Scholar were used to compile the literature. The resulting articles (1448) underwent a 4-step appraisal process and resulted in 19 articles that fitted our inclusion criteria. Microclimate variables and thermal comfort indicators were the most researched topics (discussed in 89% of studies); 47% of studies addressed cattle behavior and 36% physiological responses. Our review highlights different benefits of silvopastoral systems for grazing dairy cows. For example, the SPS provides a more comfortable thermal environment than treeless pasture, which increases feeding behaviors; furthermore, dairy cows in SPS show lower drinking events, surface temperature, and respiratory rate than cows raised in treeless pasture. However, for nine of the variables related to cows’ behavior (e.g., resting, rumination) and physiology responses (e.g., internal temperature), the results of the studies were unclear. Furthermore, behaviors associated with lying down (e.g., idling and rumination) and milk production in SPS were explored only in six and two studies, respectively. These findings provide consistent evidence that the silvopastoral systems are beneficial to thermal comfort of dairy cows; nonetheless, the effect on cows’ behavioral and physiological responses is still scarce and unclear.
Keywords: Agroforestry systems; Biometeorology; Heat abatement; Livestock farming; Milking; Natural shade